Regional Productive Complementarity and Competitiveness - Baumann, Renato; Ng, Francis (Taylor and Francis, 2013)
A positive international environment favors growth of the several economies in a given region, but it does not assure that the differences in the economic potential of the several countries are reduced in this process. Alternatively, the presence of productive complementarities might foster competitiveness and contribute to increasing the degree of homogeneity, even in situations of adverse terms of trade. This article reviews the experience of six sub-regional groups in Asia and Latin America in the last two decades. Latin America has recently benefitted from significant improvement in terms of trade and yet the economies in that region remain as different in their relative economic potential as they were in the beginning of the 1990s. In Asia, however, the negative impact of terms of trade has not blocked a quite fast pace of GDP growth; furthermore, productive complementarity has led to an increasing convergence of the several economies, with a sharp increase in their share of the international market. There are clear lessons from the Asian experience.